A transect across the landscape: the line of the A830 improvements (Scottish Historical and Archaeological Internet Reports, 2005)
The position of the new road line provided an opportunity to test the idea of a core settlement area in Arisaig surrounded by less-favoured land. The road line starts within the proposed core at its south end and then runs northwards out into an apparently 'bank' area where the archaeological potential might be predicted to be low.